ATF3 is positively involved in particulate matter-induced airway inflammation in vitro and in vivo. (1st May 2018) - Yan, Fugui; Wu, Yinfang; Liu, Huiwen; Wu, Yanping; Shen, Huahao; Li, Wen
Highlights: PM significantly upregulated ATF3 expression in HBE cells and mouse lung tissues. ATF3 has promoting effects in PM-induced airway inflammation in vitro an in vivo . ATF3 mediated PM-induced inflammatory partly through NF-κB and AP-1 pathways. Abstract: Airborne particulate matter (PM) has been reported to be associated with a wide range of respiratory disorders. However, the mechanisms underlying PM-induced airway inflammation remain largely unknown. Generally, ATF3 negatively regulates pro-inflammatory cytokines production in response to TLR4 signaling. Here we first showed ATF3 has promoting effects in PM-induced airway inflammation in vitro an in vivo . We demonstrated PM significantly upregulated ATF3 expression in HBE cells and in mouse lung tissues. ATF3 siRNA markedly inhibited, while ATF3-recombinant over-expression plasmid significantly increased PM-induced IL-6 expression in cultured HBE cells, and PM-induced IL-6, CXCL2 expression as well as neutrophil infiltration, mucus over-production in the lung of ATF3 −/− mice were all notably reduced relative to the wild-type littermates. Furthermore, we showed ATF3 mediated PM-induced inflammatory cytokines expression partly through NF-κB and AP-1 pathways. Our data further elucidates the mechanisms underlying PM-induced airway inflammation, and indicates ATF3 may function as different role in response to different stimuli.